Analisis Faktor-Faktor Yang Berpengaruh Terhadap Kinerja Keuangan UMKM Sektor Perdagangan Di Kabupaten Boyolali - Ningsih, Suhesti; Wati, Eka Susilo; Pardanawati, Sri Laksmi (Jurnal Akuntansi dan Pajak, 2024)
This purpose of the research to assess the influence of financial management, financial literacy and intellectual capital on the financial performance of UMKM in Boyolali Regency. The population of Boyolali Regency UMKM in the trade sector is 15,271 units. In this research, the sample used was 100 UMKM units, where the sample was determined based on the Slovin formula calculation. Meanwhile, the data collection method applied in this research is quantitative data with descriptive statistical analysis methods, validity tests, reliability tests and classical assumption tests. In testing the research hypothesis using multiple linear regression analysis, F test, t test and coefficient of determination test. Based on the t test that has been carried out, the research results obtained state that financial management, financial literacy and intellectual capital have a positive and significant effect on financial performance. Keywords : Financial Performance, Financial Literacy,Intellectual Capital, Financial Management